The effect of wind on jumping distance in ski jumping - fairness assessed - Virmavirta, M.; Kivekäs, J. (Sports Biomechanics, 2012)
The special wind compensation system recently adopted by Fédération Internationale de Ski (FIS; International Ski Federation) to consider the effects of changing wind conditions has caused some controversy. Here, the effect of wind on jumping distance in ski jumping was studied by means of computer simulation and compared with the wind compensation factors used by FIS during the World Cup season 2009/2010. The results showed clearly that the effect of increasing head/tail wind on jumping distance is not linear: +17.4 m/ - 29.1 m, respectively, for a wind speed of 3 m/s. The linear formula used in the trial period of the wind compensation system was found to be appropriate only for a limited range of jumping distances as the gradient of the landing slope slows down the rate of distance change in long jumps.